2012
DOI: 10.1007/s00595-012-0159-z
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey regarding the current status and controversial issues concerning reconstruction after gastrectomy in Japan

Abstract: The Japanese Society for the Study of Postoperative Morbidity after Gastrectomy conducted a nationwide questionnaire survey to clarify the current status of reconstruction after gastrectomy. One hundred and forty-five institutions (66%) responded to the survey. The questionnaire dealt with the reconstruction after a distal gastrectomy, pylorus-preserving gastrectomy (PPG), total gastrectomy, and proximal gastrectomy. The most common method of reconstruction after distal gastrectomy was Billroth I in 112 instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 23 publications
2
68
0
1
Order By: Relevance
“…c Distribution of the left gastric artery (LGA) and the right gastric artery (RGA) at the lesser curvature of the stomach gastric stasis that mainly depends on esophagogastric anastomosis remains a potential disadvantage [24]. Several reconstruction methods, such as jejunal interposition [9,16] or the double tract method [25], are used to prevent regurgitation of the gastric contents, but these procedures are slightly complicated and no general agreement exists regarding the optimal reconstruction procedures. The reasons why on -third of patients with a T1 U tumor received total gastrectomy in our institute may be related to this problem.…”
Section: Discussionmentioning
confidence: 99%
“…c Distribution of the left gastric artery (LGA) and the right gastric artery (RGA) at the lesser curvature of the stomach gastric stasis that mainly depends on esophagogastric anastomosis remains a potential disadvantage [24]. Several reconstruction methods, such as jejunal interposition [9,16] or the double tract method [25], are used to prevent regurgitation of the gastric contents, but these procedures are slightly complicated and no general agreement exists regarding the optimal reconstruction procedures. The reasons why on -third of patients with a T1 U tumor received total gastrectomy in our institute may be related to this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who undergo gastrectomy often suffer from PGS, resulting in a decrease in their QOL [13]. Therefore, function-preserving operations including PPG have been introduced to prevent this syndrome [1,5,7].…”
Section: Discussionmentioning
confidence: 99%
“…There are various reconstruction techniques that can be used after proximal gastrectomy, including esophagogastrostomy, jejunal interposition, double tract, and jejunal pouch interposition (JPI). A nationwide survey in Japan revealed that JPI was the most common reconstruction method in only 7% of 154 institutes surveyed; in comparison, 49% of institutes reported esophagogastrostomy as the most common technique 4) . However, to prevent reflux esophagitis, jejunal interposition is generally required when the remnant stomach is less than onethird of the entire stomach 4) .…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide survey in Japan revealed that JPI was the most common reconstruction method in only 7% of 154 institutes surveyed; in comparison, 49% of institutes reported esophagogastrostomy as the most common technique 4) . However, to prevent reflux esophagitis, jejunal interposition is generally required when the remnant stomach is less than onethird of the entire stomach 4) . In this context, although it is not frequently performed, the interposition of the jejunum with or without pouch formation remains an important reconstruction option.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation